Proteinase-Activated Receptor-1 and Immunomodulatory Effects of a PAR1-Activating Peptide in a Mouse Model of Prostatitis - M. Mark Stanton; Lisa K. Nelson; Hallgrimur Benediktsson; Morley D. Hollenberg; Andre G. Buret; Howard Ceri (Hindawi Limited, 2013)
Background. Nonbacterial prostatitis has no established etiology. We hypothesized that proteinase-activated receptor-1 (PAR1) can play a role in prostatitis. We therefore investigated the effects of PAR1 stimulation in the context of a new model of murine nonbacterial prostatitis. Methods. Using a hapten (ethanol-dinitrobenzene sulfonic acid- (DNBS-)) induced prostatitis model with both wild-type and PAR1-null mice, we examined (1) the location of PAR1 in the mouse prostate and (2) the impact of a PAR1-activating peptide (TFLLR-NH2: PAR1-TF) on ethanol-DNBS-induced inflammation. Results. Ethanol-DNBS-induced inflammation was maximal at 2 days. In the tissue, PAR1 was expressed predominantly along the apical acini of prostatic epithelium. Although PAR1-TF on its own did not cause inflammation, its coadministration with ethanol-DNBS reduced all indices of acute prostatitis. Further, PAR1-TF administration doubled the prostatic production of interleukin-10 (IL-10) compared with ethanol-DNBS treatment alone. This enhanced IL-10 was not observed in PAR1-null mice and was not caused by the reverse-sequence receptor-inactive peptide, RLLFT-NH2. Surprisingly, PAR1-TF, also diminished ethanol-DNBS-induced inflammation in PAR1-null mice. Conclusions. PAR1 is expressed in the mouse prostate and its activation by PAR1-TF elicits immunomodulatory effects during ethanol-DNBS-induced prostatitis. However, PAR1-TF also diminishes ethanol-DNBS-induced inflammation via a non-PAR1 mechanism by activating an as-yet unknown receptor.